eCM 2013
DOI: 10.22203/ecm.v026a19
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor and bone marrow stromal cells in osseointegration of dental implants

Abstract: Titanium implants are widely used in dental clinics and orthopaedic surgery. However, bone formation surrounding the implant is relatively slow after inserting the implant. The current study assessed the effects of bone marrow stromal cells (BMSCs) with forced expression of special AT-rich sequence-binding protein 2 (SATB2) on the osseointegration of titanium implants. To determine whether SATB2 overexpression in BMSCs can enhance the osseointegration of implants, BMSCs were infected with the retrovirus encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The osteogenic differentiation of BMSCs can be enhanced by numerous endogenous and exogenous genes and these genes can thus regulate bone remodeling (Hutmacher and Garcia 2005). Previously, several studies have demonstrated that the introduction of certain exogenous genes into BMSCs could be effective in gene therapy or tissue engineering for bone defects (Prockop 1997;Reddi 1998;Byers and Garcia 2004;Xiao et al 2011;Yan et al 2013;Gong et al 2014). Leptin (LEP), a 16-kDa cytokine, was first discovered in 1994 (Zhang et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The osteogenic differentiation of BMSCs can be enhanced by numerous endogenous and exogenous genes and these genes can thus regulate bone remodeling (Hutmacher and Garcia 2005). Previously, several studies have demonstrated that the introduction of certain exogenous genes into BMSCs could be effective in gene therapy or tissue engineering for bone defects (Prockop 1997;Reddi 1998;Byers and Garcia 2004;Xiao et al 2011;Yan et al 2013;Gong et al 2014). Leptin (LEP), a 16-kDa cytokine, was first discovered in 1994 (Zhang et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that osteogenic differentiation of BMSCs can be induced by overexpressing endogenous and exogenous genes, which can be applied to the repair of bone defects 14 , 15 . Leptin (LEP) is a 16‐kDa cytokine that plays important roles in modulating energy metabolism and appetite, as well as regulating vascular function, reproduction, immune response, and bone and cartilage formation by acting on mesenchymal stem cells 16 and differentiated cells 17 .…”
mentioning
confidence: 99%